2021
DOI: 10.1002/jsfa.11170
|View full text |Cite
|
Sign up to set email alerts
|

Potential opportunities of thinned clusters in viticulture: a mini review

Abstract: Crop thinning is a common practice performed in the vineyard consisting of whole clusters or individual fruits being removed after flowering is attained. Current studies have reported that unripe grape products as verjuice and sour grape sauce contain high content of bioactive compounds such as polyphenols, sugars, organic acids, nitrogenous compounds and sterols. This mini‐review overviewed the bioactive components obtained from thinned unripe grapes such as phenolic compounds, sugars, organic acids, minerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Many fruit species support a variable amount of fruit and have self-regulatory mechanisms for natural fruit dropping. However, trees are frequently unable to support fruit productivity using only self-regulating mechanisms [ 3 , 4 , 5 , 6 , 7 , 8 ]. For most horticultural crops, relying on falling off by themselves prevents an optimal crop load for the production of ripe fruits, with a balance of quality and quantity, and exogenous intervention is needed to achieve these goals.…”
Section: Introductionmentioning
confidence: 99%
“…Many fruit species support a variable amount of fruit and have self-regulatory mechanisms for natural fruit dropping. However, trees are frequently unable to support fruit productivity using only self-regulating mechanisms [ 3 , 4 , 5 , 6 , 7 , 8 ]. For most horticultural crops, relying on falling off by themselves prevents an optimal crop load for the production of ripe fruits, with a balance of quality and quantity, and exogenous intervention is needed to achieve these goals.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the quality of table grapes, fruit thinning is an indispensable cultivation and management step in the process of growing and developing fresh grapes. In the process of fruit thinning, if part of the developing young fruit is removed, the remaining young fruit can use more photosynthates, resulting in larger fruit grains and a more uniform fruit quality ( Gutiérrez-Gamboa, Wei, Moreno-Simunovic, Sun, & Fang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TUR gradually attracts people's attention ( Bovo et al, 2016 , Fia et al, 2021 , Gutiérrez-Gamboa et al, 2020 , Piccardo et al, 2019 , Tinello and Lante, 2017 ) and becomes an urgent problem for the grape industry. Previous studies have revealed that grape juice made from TUR could be used as food-flavoring agent ( Dupas de Matos et al, 2018 ), such as replacing vinegar to make salad dressings and pickles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations